Legal Re-Construction; The Impact of Empty Column Victory Over Single Candidates in Simultaneous Direct Elections of Regional Heads as A New Phenomenon of Legal Politics in Indonesia : (Case Study: Makassar City) - Jaya, Apriliani Kusuma; Ilyas, Ilyas (International Journal of Business, Law, and Education, 2024)
This study examines the legal re-construction of the victory impact of an empty column over a single candidate as a new phenomenon of legal politics in Makassar City, South Sulawesi, Indonesia. This is a doctrinal normative legal research, which uses the analytical, explorative, explanatory, and qualitative analysis techniques. The result showed that legal reconstruction needs to be carried out on disputes, policies of single candidate pairs and empty columns, nomination requirements and political party support for candidates. The legal construction also needs to be conducted on the phrase "next election," the emptiness of definitive city government leaders, postponement and legal uncertainty, establishment of Provisional Acts (Pjs), as well as the loss of the constitutional rights of communities and regions.. Legal reconstruction also needs to be carried out through the political management of post-conflict local elections with changes in legal policies Law No.10 of 2016, PKPU No.13 of 2018, Minister of Home Affairs Regulation (Permendagri) No. 1 of 2018.